2021
DOI: 10.1210/jendso/bvab082
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Obstructive Sleep Apnea and Continuous Positive Airway Pressure Therapy on Skeletal Muscle Lipid Content in Obese and Nonobese Men

Abstract: Obstructive sleep apnea (OSA), independently of obesity (OBS), predisposes to insulin resistance (IR) for largely unknown reasons. Since OSA-related intermittent hypoxia triggers lipolysis, overnight increases in circulating free fatty acid (FFA) including palmitic acid (PA) may lead to ectopic intramuscular lipid accumulation potentially contributing to IR. Using 3-T-1H-magnetic-resonance-spectroscopy, we therefore compared intra- and extra-myocellular lipid (IMCL and EMCL) in vastus lateralis muscle at ~7:00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Triglycerides were specifically analyzed due to a strong relationship between waist circumference and triglycerides, likely mediated through insulin resistance 41 and due to the minimal effects of lipid lowering therapies compared to other lipid measures. We further conducted binary logistic regression to determine associations between clinical categories of OSA [no OSA <10/hr, mild (10-19/hr), moderate (20-29/hr) and severe (≥30/hr) (27)] and the categorized dependent variable -triglyceride (≥ 1.7mmol/L).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Triglycerides were specifically analyzed due to a strong relationship between waist circumference and triglycerides, likely mediated through insulin resistance 41 and due to the minimal effects of lipid lowering therapies compared to other lipid measures. We further conducted binary logistic regression to determine associations between clinical categories of OSA [no OSA <10/hr, mild (10-19/hr), moderate (20-29/hr) and severe (≥30/hr) (27)] and the categorized dependent variable -triglyceride (≥ 1.7mmol/L).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Supporting this, a recent study using early morning 3-T-1 H-magnetic resonance spectroscopy of the vastus lateralis muscle in men reported substantial and most likely transient increases of intramyocellular and extramyocellular lipids in non-obese men with OSA compared to participants without OSA. 27 Consequently, we conducted analyses stratified by waist circumference to observe an obesity-independent association between OSA metrics and dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fractional clearance rate (FCR) of TG showed a 5-fold increase after 3-month CPAP therapy, but the FCR of CE was unchanged [ 109 ]. Circulating FFAs, which are the markers of increased lipolysis, were decreased after CPAP [ 345 ]. In line with this, CPAP withdrawal dynamically increased nocturnal FFA levels [ 346 ].…”
Section: The Effect Of Osa Therapy On the Lipid Metabolismmentioning
confidence: 99%
“…Our results complement a recent study showing (in agreement with the present study) that OSA worsens glucose homeostasis. However, other authors also observed increased intra- and extramyocellular lipid content in skeletal muscle [ 61 ]. An increased triglyceride accumulation and modified lipidomic profile in myocytes after hypoxic exposure has been documented in vitro, presumably partly due to de novo lipogenesis [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%